Feasibility and safety of left atrial posterior wall isolation with a new Cryoballoon technology in patients with persistent atrial fibrillation. Issue 5 (7th April 2022) - Bisignani, Antonio; Pannone, Luigi; Miraglia, Vincenzo; Sieira, Juan; Iacopino, Saverio; Bala, Gezim; Ströker, Erwin; Overeinder, Ingrid; Almorad, Alexandre; Gauthey, Anaïs; Monaco, Cinzia; Paparella, Gaetano; et al.
Abstract: Background: Left atrial posterior wall isolation (LAPWI) is often performed in addition to pulmonary vein isolation (PVI) in the setting of persistent atrial fibrillation (AF) ablation. The aim of this study was to evaluate the feasibility and safety of a new cryoballoon ablation system in achieving PVI + LAPWI isolation. Methods: The study was a prospective, non‐randomized, single center study. Forty consecutive patients, undergoing PVI + LAPWI with the novel POLARx™, were compared to 40 consecutive patients who underwent the same procedure with the established Arctic Front Advance PRO™. Results: Acute isolation was achieved in all PVs in both groups and left posterior wall isolation (LAPWI) was achieved in 38 patients (95%) in the POLARx group and in 36 patients (90%) in Arctic Front group. Procedural outcomes were similar between both groups, except for lower temperatures during cryoenergy in the POLARx group, for both pulmonary vein isolation (PVI) and LAPWI. Conclusion: LAPWI + PVI with the novel POLARx™ Cryoballoon is feasible and safe; the results are comparable with the Arctic Front Advance PRO™ system.